1984
DOI: 10.1016/0014-5793(84)80111-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of lysine residues in the binding of ovine chorionic somatomammotropin to lactogenic and somatotropic receptors

Abstract: The biological activities of several ovine chorionic somatomammotropin (oCS) derivatives obtained by chemical modification of the lysine residues were studied by radioreceptor assays using rabbit mammary homogenates (lactogenic activity, L.A.) and liver homogenates (somatotropic activity, S.A.). Even if the control treatment with BHI markedly decreased the L.A., it was clear that methylation mainly affected the S.A. and that ethylation reduced both activities. Guanidination inactivated almost completely both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…lodination of 3 tyrosine residues of bGH does not interfere with the structure of this hormone, which exhibits a similar circular dichroism spectrum and does not modify its activity for somatotropic sites . Biscoglio de Jimenez Bonino et al (1979) have observed a 50% reduction in n vivo in the bGH growth activity after trinitrophenylation of lysines 181, 145, 70, 113, 172 and 168 (Chene et aL, 1984;Martal e t al., 1985). They showed that whatever the degree and kind of chemical modification, lysine residues participate in the hormone-hepatic receptor interaction.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…lodination of 3 tyrosine residues of bGH does not interfere with the structure of this hormone, which exhibits a similar circular dichroism spectrum and does not modify its activity for somatotropic sites . Biscoglio de Jimenez Bonino et al (1979) have observed a 50% reduction in n vivo in the bGH growth activity after trinitrophenylation of lysines 181, 145, 70, 113, 172 and 168 (Chene et aL, 1984;Martal e t al., 1985). They showed that whatever the degree and kind of chemical modification, lysine residues participate in the hormone-hepatic receptor interaction.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%